2016
DOI: 10.1027/1016-9040/a000263
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Behavioral, Experiential, and Conceptual Dimensions of the Self

Abstract: Abstract. The self has become a prominent field of research in psychology but despite its eminent first-person character, it is typically studied from a third-person perspective. Such a third-person approach is well suited to enquire into the behavioral expression of the sense of selfhood but it does not capture the core experience – the so-called qualia nature – of the self. In the current article we illuminate the challenges that a predominant third-person approach poses to an understanding of the self. We o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 32 publications
(48 reference statements)
0
24
0
Order By: Relevance
“…The systematic training of introspective competencies has been revealed to be an effective way of improving introspection. Weger et al (2016) demonstrate how such training improves first-person access to one's mental processes. They implemented five exercises based on meditative concentration.…”
Section: Training Of the Subject's Introspective Competenciesmentioning
confidence: 92%
See 3 more Smart Citations
“…The systematic training of introspective competencies has been revealed to be an effective way of improving introspection. Weger et al (2016) demonstrate how such training improves first-person access to one's mental processes. They implemented five exercises based on meditative concentration.…”
Section: Training Of the Subject's Introspective Competenciesmentioning
confidence: 92%
“…Here, the training of the subject's introspective competencies is one of the most promising ways of improving a subject's access to conceptual knowledge. Previous research has revealed that the systematic training of introspective competencies succeeds in improving first-person access to one's own mental processes (Weger et al, 2016). On the other hand, it has not been recently clear how introspective reporting may be biased by the specific styles of training introspective competencies.…”
Section: Elimination Of Attentional Attributional Conceptual and Ementioning
confidence: 99%
See 2 more Smart Citations
“…What we have been doing in experimental psychology, however, is largely keeping our standards unchanged and imposing them on a phenomenon that is not really done justice through these third‐person methods. In turn, phenomena that have a primary first‐person or qualia character such as mind wandering (but also other phenomena, e.g., consciousness or the self) are ultimately misunderstood or only partially understood, as we will outline later on (see also Weger, Meyer, & Wagemann, ). New methods are needed to deal with such phenomena.…”
Section: Introductionmentioning
confidence: 99%